Parental Phubbing and Adolescent Depressive Symptoms during COVID-19: A Serial Meditating Model - Wencheng Yang; Lu Tang; Xiangping Shen; Gengfeng Niu; Xiaohan Shi; Siyu Jin; Yumang Zhang; Zihui Yuan (Behavioral Sciences, 2023)
Background: During the COVID-19 pandemic, depressive symptoms, a common emotional problem among adolescents, have become more prominent. Regarding the influencing factors of adolescent depressive symptoms, it is widely accepted that parents’ problematic cellphone use around the family (specifically parental phubbing) is a strong predictive factor for the development of depressive symptoms among adolescents. Notably, the COVID-19 pandemic caused a sharp increase in the number of individuals with depressive symptoms, and the negative consequences of parental phubbing and depressive symptoms might have been exacerbated. Accordingly, this study aimed to examine the association between parental phubbing and adolescent depressive symptoms as well as their underlying mechanism. Method: To test our hypotheses, we conducted an offline/online survey with 614 adolescents in Central China from May to June 2022, which corresponded to a period of strict lockdowns in some areas due to the outbreak of the Omicron variant. The participants completed a set of measures, including a technology interference questionnaire, a parent–child relationship scale, a self-concept clarity scale, and the depressive symptoms scale. Results: Parental phubbing was positively associated with adolescent depressive symptoms; the parent–child relationship and self-concept clarity could independently mediate this relationship; and the parent–child relationship and self-concept clarity were also serial mediators in this association. These findings extend previous research by highlighting the impact of parental technology use on their children and the underlying mechanism explaining adolescent depressive symptoms. They provide practical recommendations for parents to prioritize fostering a positive family environment and minimizing phubbing behaviors to enhance adolescent development, particularly in the context of the COVID-19 pandemic.